Giardia intestinalis genotypes: risk factors and correlation with clinical symptoms - Mahdy, A.K.M.; Surin, J.; Wan, K.L.; Mohd-Adnan, A.; Al-Mekhlafi, M.S.H.; Lim, Y.A.L. (2009)
This study was conducted to identify genotypes related risk factors of Giardia intestinalis in an Orang Ash (aboriginal) community in Pahang, Malaysia. Stool samples were collected from 321 individuals aged between 2 and 76 years old, of whom 160 were males and 161 were females. Faecal samples were processed with trichrome staining technique for the primary identification of G. intestinalis. Molecular identification was carried out by the amplification of a partial SSU rRNA gene using nested PCR. PCR products were purified and genotyped. 42 samples successfully amplified from the 76 positive faecal samples, only 1 was Assemblage A, the rest were Assemblage B. Risk analysis based on the detected genotypes of Giardia using univariate analysis and logistic regression identified three significant risk factors of giardiasis caused by assemblage B which included children <= 12 years (OR=13.56, 95 CI=1.79-102.64, p=0.012), females (OR=2.52, 95 CI=1.11-5.75, p=0.027) and eating fresh fruits (OR=7.78, 95 CI=1.01-60.00, p=0.049). Assemblage B infection was significantly correlated with clinical symptoms of giardiasis (OR=2.4, 95 CI=1.13-5.12, p=0.019). Females infected with Assemblage B were at higher risk of manifesting gastroenteritis signs and symptoms (OR= 3.9, 95 CI =1.50-10.31, p =0.004). It has been concluded that giardiasis is still a public health problem in Orang Ash community and most commonly caused by assemblage B. The dynamic of transmission is most probably anthroponotic which is human to human either directly or indirectly through contaminated food. This route of transmission should be considered in the control strategy of the disease. Mass treatment together with health education could be the most practical intervention for reducing the infection. Those at high risk should receive more attention from public health authorities. (C) 2009 Elsevier B.V. All rights reserved.